A Well-Behaved Anisotropic Strange Star Model - Amos V. Mathias; Jefta M. Sunzu (Advances in Mathematical Physics)
We obtain a new nonsingular exact model for compact stellar objects by using the Einstein field equations. The model is consistent with stellar star with anisotropic quark matter in the absence of electric field. Our treatment considers spacetime geometry which is static and spherically symmetric. Ansatz of a rational form of one of the gravitational potentials is made to generate physically admissible results. The balance of gravitational, hydrostatic, and anisotropic forces within the stellar star is tested by analysing the Tolman-Oppenheimer-Volkoff (TOV) equation. Several stellar objects with masses and radii comparable with observations found in the past are generated. Our model obeys different stability tests and energy conditions. The profiles for the potentials, matter variables, stability, and energy conditions are well behaved.